Micro‐CT measurements of tumoral vessels supplied by portal circulation in hepatic colorectal metastasis mouse model. Issue 6 (21st March 2014) - Jun, Hong Young; Lee, Young Hwan; Juhng, Seon Kwan; Lee, Myeung Su; Oh, Jaemin; Yoon, Kwon‐Ha
ABSTRACT The purpose of this study was to elucidate the micro CT findings of tumoral vessels supplied by portal circulation during establishment of hepatic metastasis of colorectal cancer in a mouse model. Hepatic metastases were induced in 15 BALB/c mice through the injection of murine colonic adenocarcinoma tumor cells into the mesenteric vein. Micro‐CT imaging of the tumoral vessels was obtained to clarify the microvascular architecture. We evaluated the sinusoidal structure, diameter of the tumoral vessels (DTV) and blood vessel density (BVD) according to tumor sizes ranging from 201 to 3, 000 µm in diameter. A total of 116 tumors were observed on day 15 after cell injection. The mean diameter of a normal hepatic sinusoid was 11.7 ± 2.0 µm on micro CT. The DTV supplied by the portal vein of tumors measuring 1, 001–1, 500 µm in diameter was greater than that of tumors 200–1, 000 µm in diameter. The mean BVD from the portal vein gradually decrease according to size of tumor from 201 to 3, 000 µm in diameter (r2 = −0.584, P < 0.01). The characteristics of tumoral vessels supplied by portal circulation during establishment of hepatic colorectal metastases were well visualized with micro‐CT imaging. Microsc. Res. Tech. 77:415–421, 2014. © 2014 Wiley Periodicals, Inc.